Experts and resource users split over solutions to peatland fires - Phelps, J.; Zabala, A.; Daeli, W.; Carmenta, R. (Elsevier, 2021)
We provide empirical evidence that supports a commonly-held assumption: that experts’ appraisals of policy options are often very distinct from those of resource users most affected by those policy choices. We analyse perspectives about 40 policy options to address peatland fires in Indonesia, using a Q methodology approach to rank the options according to perceived effectiveness. Peatland fires in Indonesia are a long-standing and complex social-ecological challenge, where unsolved disagreements about policy options have profound implications for environmental governance, resulting in fires recurring and causing significant CO2 emissions and transboundary haze that affects the health of millions. We collected data from 219 respondents, covering twelve stakeholder categories, including small and large landholders, industrial farmers, scientists, local leaders and government officials. We identified the most representative response from each stakeholder category, and used hierarchical cluster analysis to explore the closeness/distance in perspectives among categories. The results show a particularly noticeable distinction between two broad groups, which we labelled as experts and resource users. Experts tend to prefer solutions that are centralised and largely transformative, whereas resource users favour more localised measures that are more compatible with business-as-usual. We discuss possible reasons for these differences, and their implications for environmental governance, including for how scientists engage in policy.